The Effect of Infographics on English Speaking Ability at Majapahit Islamic University - Muchammad Irawan, Ambang; Lindawati, Rini; Ganinda, Nurhayati (PT. Kreasi Karya Majakata, 2024)
The purpose of this study was to investigate the effects of using infographics as a supporting media in improving the speaking skills of English language education students. This study was conducted using the Quantitative Method by distributing questionnaires to 30 English language education students from various semesters. The results of the study showed that the use of Infographic media has a positive effect on English speaking skills at Majapahit Islamic University with a Pearson correlation test value of 0.331. It is proven that infographics can improve English speaking skills. The results show that infographic media can be used to improve students' speaking skills in speaking English.